Predictors of undergraduates' intention to incorporate glycaemic index into dietary behavior - Goodwin, R.; Mullan, Barbara (Wiley-Blackwell Publishing Asia, 2009)
Aim: The present study used an extension of the theory of planned behaviour to analyse undergraduates’ intention to perform behaviour related to the glycaemic index of food. The extended model incorporated measures of past behaviour and pre-existing knowledge about glycaemic index. Methods: Seventy-two participants read an academic journal article about glycaemic index and completed questionnaires measuring predictor components of the theory of planned behaviour model. Results: Subjective norm and attitude were generally observed to be the best predictors of intention. Pre-existing knowledge about glycaemic index and attitude towards restrained eating were generally found to be poor predictors of intention. Past behaviour exhibited a positive relationship with intention. Conclusions: Interventions that focus on dietary behaviour related to the glycaemic index of food should involve individuals who have relationships of influence with the target demographic, such as friends and family, and will need to address modifying ingrained patterns of behaviour.